2013
DOI: 10.3389/fphys.2013.00086
|View full text |Cite
|
Sign up to set email alerts
|

Time scales in cognitive neuroscience

Abstract: Cognitive neuroscience boils down to describing the ways in which cognitive function results from brain activity. In turn, brain activity shows complex fluctuations, with structure at many spatio-temporal scales. Exactly how cognitive function inherits the physical dimensions of neural activity, though, is highly non-trivial, and so are generally the corresponding dimensions of cognitive phenomena. As for any physical phenomenon, when studying cognitive function, the first conceptual step should be that of est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 91 publications
0
40
0
Order By: Relevance
“…The scale invariance of neuronal avalanches enables their detectability even at large-scale activity of the entire human cortex observed using noninvasive neuroimaging methods. Recently, using MEG, cortical activity of healthy human subjects was shown to consist of neuronal avalanches at both the sensor (Shriki et al, 2013) and the source level (Palva et al, 2013), suggesting that it is in a critical state. Here, we were able to demonstrate that the human brain maintains critical dynamics during different cognitive states, namely, rest and stimulus-evoked.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The scale invariance of neuronal avalanches enables their detectability even at large-scale activity of the entire human cortex observed using noninvasive neuroimaging methods. Recently, using MEG, cortical activity of healthy human subjects was shown to consist of neuronal avalanches at both the sensor (Shriki et al, 2013) and the source level (Palva et al, 2013), suggesting that it is in a critical state. Here, we were able to demonstrate that the human brain maintains critical dynamics during different cognitive states, namely, rest and stimulus-evoked.…”
Section: Discussionmentioning
confidence: 99%
“…Data processing and analysis were performed using MATLAB 2011b (MathWorks) and FieldTrip open-source toolbox for Advanced MEG Analysis (Oostenveld et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are examples of fractals in physiology (e.g., Goldberger et al 2002;Ivanov et al 2001;Papo 2013;Peng et al 1994Peng et al , 2002; intraperson behavior (Aks et al 2002;Delignières et al 2008;Gilden et al 1995;Gilden 2001Gilden , 2009Ihlen and Vereijken 2010;Kello et al 2007;Torre et al 2007;Torre and Wagenmakers 2009;Anastas et al 2011;Valdez and Amazeen 2008, 2010Van Orden et al 2003); interperson behavior (e.g., Fine et al 2015;Gorman et al 2010;Likens et al 2014;Marmelat and Delignières 2012); and countless other non-human processes (Bak 1997;Mandelbrot 1983;Solé and Goodwin 2000). Thus, it is no wonder that some researchers investigating fractal phenomena use words like "ubiquitous" (Van Orden et al 2003;Van Orden 2010) and "pervasive" (Kello et al 2008) in favor of "idiosyncratic" (Torre and Wagenmakers 2009).…”
Section: What Is Not Fractal?mentioning
confidence: 97%
“…It was shown that the probability that a particular number of cortical areas are recruited into an OM (defined as the temporal RTP coincidences) is governed by power-law statistics [69]. Such dependency is characteristic for non-ergodic systems, thus suggesting, in contrast to a traditional understanding of the brain as an ergodic system [27], that brain functional activity is rather non-ergodic [70,71]. Further, our analysis revealed that such stabilized spatiotemporal OM configurations also have the transient dynamic which is expressed as a series of sudden transitions between OMs [22].…”
Section: Empirical Supportmentioning
confidence: 97%